Development and characterization of parenteral nano-delivery system loaded with azithromycin - Daood, Ghaidaa S (2016)
The blood brain barrier (BBB) is established by brain microvascular endothelial cells (BMEC) working simultaneously with pericytes and astrocytes, in which tight junctions and several transporters strictly regulate the penetration of various bioactive compounds into the brain including antibiotics. This has significant consequences for the treatment of Central Nervous System (CNS) infections, as antibiotics have to gain access to the brain through the BBB in adequate concentrations to exhibit their antibacterial activity. Azithromycin (AZO) is a broad spectrum antibiotic with a unique pharmacokinetic profile. However, its role in treatment of CNS infections is limited because it does not possess the appropriate physicochemical properties that enables it to achieve sufficient concentrations in brain tissue. Nanoemulsion system is one of the potential strategies for efficient delivery of lipophilic actives across the BBB owing to their nano-sized, biocompatible, biodegradable, physical stability and relatively easy to produce on a large scale. With the aim of brain targeting, AZO-loaded nanoemulsions were developed utilizing high pressure homogenization with a homogenization pressure of 1000 bar for 8 cycles. The formulated nanoemulsions were optimized utilizing artificial neural network (ANN) as a multivariate statistical technique. In order to achieve the optimum topologies, ANN was trained by Incremental Back-Propagation (IBP), Batch Back-Propagation (BBP), Quick Propagation (QP), and Levenberg- Marquardt (LM) algorithms for testing data set. The topologies were confirmed by the indicator of minimized root mean squared error (RMSE) for each. Based on that indicator, the BBP-5-14-1 was selected as the optimum topology to be used as a final model to predict the desirable particle size and relative importance of the formulation’s effective variables. The ANN analysis showed that with optimum compositions of soya bean oil 6%, oleic acid 2%, AZO 1.4%, lecithin 2%, Tween 80 2%, glycerol 2.5%, vitamin E 0.25%, and water 83.85%, minimum particle size can be obtained. The optimized nanoemulsions were evaluated for the various physicochemical properties. The characterization revealed particle size of 54.67 ± 0.81 nm, polydispersity index (PDI) of 0.218 ± 0.023, zeta potential of -34.65 ± 0.78 mV, pH of 7.82 ± 0.07, viscosity of 1.77 ± 0.05 cps, and osmolality of 288 ± 1.00 mOsm/kg, suggesting their compatibility for intravenous administration. AZO was successfully incorporated into nanoemulsion system with an average encapsulation efficiency of 98.21 ± 1.97% and a relatively high drug loading of 91.19 ± 5.93%. Morphological analysis with Transmission Electron Microscopy (TEM) confirmed the formation of almost spherical shaped uniformly distributed nano-sized oil droplets. In vitro drug release study of the selected formulation demonstrated a release profile similar to that of AZO standard solution, both exhibited a biphasic behavior characterized by a fast initial release of the encapsulated drug followed by a slower sustained release till the optimized formulation achieved a total accumulative release of the drug of 84.94 ± 4.76% within 48 h. Kinetically, AZO release profile from nanoemulsion system in vitro appeared to fit best with the Higuchi model. Stability of nanoemulsion prepared with the optimized formula was mainly evaluated in term of preserving its physical integrity, namely particle size and polydispersity index (PDI). The formulation maintained its properties in a satisfactory range up to 12 months of storage at 4˚C and 25˚C, which demonstrated sufficient physical stability upon long-term storage. A linear relationship between the particle size (cube of the radius of dispersed phase droplets (r3)) and time (t) was obtained identifying Ostwald ripening (OR) as the dominant destabilization mechanism of AZO-loaded nanoemulsion from a 12-months shelf-life study. OR rate (ω) was extrapolated graphically from the slope and was found to be 0.232 ×10-8 nm3/s. Optimized nanoemulsion was analyzed for its drug content to monitor its chemical stability. The shelf-life (t0.9) of optimized nanoemulsion formulation was estimated to be 4.85 years at 25˚C which reflected the ability of nanoemulsion formulation to maintain the drug and efficiently protected it against degradation. To summarize, the studies conducted indicate the utility and potential advantage of AZO-loaded nanoemulsion system as a promising delivery carrier worth to explore further for its parenteral applicability in the treatment of bacterial meningitis.